MEKTEPLERDE OQIWSHILARDIŃ DÓRETIWSHILIK QÁBILETIN RAWAJLANDIRIWDA STEAM TÁLIMINIŃ ÁHMIYETI - Zarımbetova, G.; Maksetova, N. (SCIENCE and SOCIETY, 2022)
The article discusses the use of modern learning technologies in the process of continuous education and the identification of students' creative abilities by the STEAM program.